2017
DOI: 10.3390/s17020278
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characterization of an xy-Stage Applied to Micrometric Laser Direct Writing Lithography

Abstract: This article concerns the characterization of the stability and performance of a motorized stage used in laser direct writing lithography. The system was built from commercial components and commanded by G-code. Measurements use a pseudo-periodic-pattern (PPP) observed by a camera and image processing is based on Fourier transform and phase measurement methods. The results report that the built system has a stability against vibrations determined by peak-valley deviations of 65 nm and 26 nm in the x and y dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Foroosh et al [15] proposed a phase correlation method on downsampled images using a Sinc function to approximate the Dirac Delta function in the frequency domain, which has less computation complexity but limited registration accuracy (0.05 pixel resolution) compared to the conventional FFT method. Guelpa et al and Jaramillo et al [29,30] demonstrated different vision measurement methods to sense 1D and 2D displacements. Subpixelic performance was derived from a phase shifting algorithm [31] applied to the images of pseudo-periodic patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Foroosh et al [15] proposed a phase correlation method on downsampled images using a Sinc function to approximate the Dirac Delta function in the frequency domain, which has less computation complexity but limited registration accuracy (0.05 pixel resolution) compared to the conventional FFT method. Guelpa et al and Jaramillo et al [29,30] demonstrated different vision measurement methods to sense 1D and 2D displacements. Subpixelic performance was derived from a phase shifting algorithm [31] applied to the images of pseudo-periodic patterns.…”
Section: Introductionmentioning
confidence: 99%
“…However, the manufacturing of this interferometer unit requires complicated alignment and bonding techniques, which makes it difficult to replicate and deploy in other sensing applications. Beyond space-based gravitational-wave observation, several other applications can benefit from such compact highsensitivity laser interferometers such as spacecraft dragfree control [9,10] or the characterization and calibration of laser direct writing lithography [11], which require precisions at or below the nanometer level, as well as dimensional metrology, and machining tools in manufacturing and precision measurements, striving precisions from picometers up to microns [12].…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of those devices requires a previous step of micropatterning. This consists in transferring a pre-defined design onto the substrate by means of techniques such as mask UVlithography, mask-less lithography systems such as laser-direct-writinglithography, and inkjet printing [5], [6]. The design corresponds, in most of the cases, to micrometric features.…”
Section: Introductionmentioning
confidence: 99%